A Framework for the Quality-Oriented Design of Micro Manufacturing Process Chains. Issue 7 (29th August 2014) - Rippel, Daniel; Lütjen, Michael; Scholz-Reiter, Bernd
Abstract : Purpose: In micro cold forming, the high degree of technological dependencies between manufacturing, quality-inspection and handling technologies leads to an extremely complex planning of process chains. In addition, the lack of standardised processes and interfaces further complicates the planning. Design/methodology/approach: In order to provide consistent and comprehensive planning of micro manufacturing processes, this article discusses a method, which integrates the planning of process-flows, the planning of technological dependencies and capabilities, as well as of the corresponding material flow. Findings: The article presents the µ-ProPlAn (Micro-Process Chain Planning and Analysis) framework. It consists of a specific modelling method, a simultaneous engineering procedure model for the model creation, as well as of methods for the analysis of technological dependencies and logistic key-values along the modelled process chains. Research limitations/implications: As the results presented in this article originate from an on-going research project, the article focusses on a detailed presentation of the modelling methodology and the procedure model. Practical implications: In practice, the µ-ProPlAn framework provides process designers in the field of micro manufacturing with tools and methods to clearly depict the interdependencies between and within a product's different manufacturing stages. Originality/value: By following a simultaneous engineering approach, µ-ProPlAn aims to reduce the efforts in process design by supporting the design of manufacturing processes in the early stages of the product design and by providing suitable methods for the analysis of these process chains.